2004
DOI: 10.1074/jbc.m311993200
|View full text |Cite
|
Sign up to set email alerts
|

Luteinizing Hormone, a Reproductive Regulator That Modulates the Processing of Amyloid-β Precursor Protein and Amyloid-β Deposition

Abstract: Hormonal changes associated with the dysregulation of the hypothalamic-pituitary-gonadal (HPG) axis following menopause/andropause have been implicated in the pathogenesis of Alzheimer's disease (AD). Experimental support for this has come from studies demonstrating an increase in amyloid-␤ (A␤) deposition following ovariectomy/castration. Because sex steroids and gonadotropins are both part of the HPG feedback loop, any loss in sex steroids results in a proportionate increase in gonadotropins. To assess wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
132
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(146 citation statements)
references
References 76 publications
12
132
1
1
Order By: Relevance
“…Consistent with this possibility, a few studies have used direct bath application of E to hippocampal slices and reported an increase in long term potentiation, a cellular model for memory (Bi et al 2000;Foy et al 1999). However, it has been suggested that estrogen in vitro suppresses LH receptors so the in vitro effect of E could still be via suppression of LH signaling (Bowen et al, 2004). Estradiol treatment of ovxed females is also known to increase hippocampal spine density Leranth et al 2000Leranth et al , 2002Woolley et al 1990;Woolley and McEwen 1992), a change that is thought to underlie changes in memory ability, but it is unknown if any of the effects of E on spine density may actually be due to changes in LH.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with this possibility, a few studies have used direct bath application of E to hippocampal slices and reported an increase in long term potentiation, a cellular model for memory (Bi et al 2000;Foy et al 1999). However, it has been suggested that estrogen in vitro suppresses LH receptors so the in vitro effect of E could still be via suppression of LH signaling (Bowen et al, 2004). Estradiol treatment of ovxed females is also known to increase hippocampal spine density Leranth et al 2000Leranth et al , 2002Woolley et al 1990;Woolley and McEwen 1992), a change that is thought to underlie changes in memory ability, but it is unknown if any of the effects of E on spine density may actually be due to changes in LH.…”
Section: Discussionmentioning
confidence: 99%
“…Aβ oligomers are reported to disrupt long term potentiation (LTP) in vitro (Wang et al, 2002(Wang et al, , 2004 and in vivo (Walsh et al, 2002), and, appear to introduce memory impairment in AD mouse models (Cleary et al, 2004). In vitro research indicates that LH may increase Aβ by driving amyloid-β precursor protein (AβPP) processing to the amyoidogenic pathway (Bowen et al, 2004). However, whether LH/hCG affects AβPP processing via LH receptors or through an LH receptor-independent pathway is not known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mice, the GnRH agonist leuprolide, which reduces gonadotropin and sex steroid levels, significantly reduced Aβ 1-42 and 1-40. Furthermore LH treatment of neuroblastoma cells in culture did not affect Aβ precursor protein (Aβpp) expression but did alter Aβpp processing toward the amyloidogenic pathway (Bowen et al 2004). A very recent paper (Casadesus et al 2006) showed that, in contrast to the adverse cognitive test results in estrogen plus progestin-treated postmenopausal women (Espeland et al 2004), suppression of LH by leuprolide significantly attenuated cognitive decline and decreased amyloid-β deposition in an aged transgenic mouse model of Alzheimer's disease compared with placebo-treated animals.…”
Section: New Information On the Direct Roles Of Gonadotrophic Hormonementioning
confidence: 99%
“…Studies in vitro using the M17 neuroblastoma cell line showed that treatment with LH increased Aβ production however the mechanism for this remains unclear (Bowen et al, 2004). Using a similar neuroblastoma cell model (SH-SY5Y), we sought to investigate specifically whether LH/hCG receptor activation triggers β-cleavage of APP.…”
mentioning
confidence: 99%